2019
DOI: 10.1111/cen.13931
|View full text |Cite
|
Sign up to set email alerts
|

Adipocyte expression of glucose transporter 1 and 4 in PCOS: Relationship to insulin‐mediated and non–insulin‐mediated whole‐body glucose uptake

Abstract: Background: Polycystic ovary syndrome (PCOS) is a highly prevalent endocrine-metabolic disorder associated with insulin resistance (IR). In IR states, non-insulin-mediated glucose uptake (NIMGU) may increase to compensate for declining insulin-mediated glucose uptake (IMGU), although this does not appear to be the case in PCOS. The underlying molecular mechanisms for this deficiency remain unclear. Objectives: To compare adipocyte glucose transporter 1 and 4 (GLUT-1 and GLUT-4) gene expression in PCOS women an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…In another paper, the same research group also compared GLUT1 and GLUT4 mRNA levels in adipocytes of PCOS women and matched controls. Their results suggest that IR secondary to lower insulinmediated glucose uptake and enhanced insulin secretion in PCOS is partly attributable to a reduction in adipocyte GLUT4 expression that is not accompanied by a compensatory increase in GLUT1 expression [30].…”
mentioning
confidence: 98%
“…In another paper, the same research group also compared GLUT1 and GLUT4 mRNA levels in adipocytes of PCOS women and matched controls. Their results suggest that IR secondary to lower insulinmediated glucose uptake and enhanced insulin secretion in PCOS is partly attributable to a reduction in adipocyte GLUT4 expression that is not accompanied by a compensatory increase in GLUT1 expression [30].…”
mentioning
confidence: 98%
“…The decrease of glucose uptake and utilization by skeletal muscle and adipocytes caused by the decrease of GLUT4 expression or activity is an important molecular basis of IR. A prospective crosssectional study showed that IR secondary to PCOS insulinmediated decreased glucose uptake and increased insulin secretion was partly due to decreased GLUT4 expression in adipocytes without a compensatory increase in GLUT1 expression (34). The analysis of signaling components of the IRS/PI3K/AKT pathway showed that the expression of GLUT4 was significantly decreased in PCOS patients and the IR control group (35).…”
Section: Discussionmentioning
confidence: 99%
“…This explains why IR is often associated with compensatory hyperinsulinemia [ 92 , 94 , 95 ]. Many studies have shown that the decrease of glucose transporter type 4 (GLUT-4) expression is one of the mechanisms underlying IR and PCOS [ 96 98 ]. Feng et al found that insulin resistance reduced the expression of sex hormone-binding protein (SHBG) in human villous trophoblast cells, thereby inhibiting the expression of GLUT-4 and phosphatidylinositol 3-kinase (PI3K) p85α mRNA.…”
Section: Npy Affects Metabolic Disordersmentioning
confidence: 99%